Assessing the impact of Volatile Functionality removal in web applications: Model‐Driven vs Code‐Based approaches. (29th June 2017) - Urbieta, M.; Frajberg, D.; Rossi, G.
Summary: Web applications must quickly adapt to new business demands to keep clients onboard. When unexpected and unforeseen requirements appear, the changes pose challenges to software engineers as they were not considered in the application design and such new functionality can be only valid only for a period in certain situations. This work presents a comparison of maintenance consequences in the software quality when using a Model‐Driven approach against a Code‐Based one where changes are managed in an ad hoc way. We used the removal of volatile functionality as case of study due to the fact that its characteristics stress the development process. We considered both external and internal quality of deliverables. For assessing the quality of deliverables, we evaluated the production of more than 35 students using both approaches considering their perception gathered through questionnaires and their deliverables. We present the preliminary evidence that there is no significant difference between approaches. Model‐Driven performed slightly better than Code‐Based, but both responded negatively in terms of deliverables' quality. Results show that maintenance tasks are detrimental to software quality where Model‐Driven approach does not excel over Code‐Based approach. The Model‐Driven approach only highlighted on productivity.